Diversity and ecological determinants of essential oil composition of Achillea millefolium from various geobotanical areas of Samarkand, Uzbekistan - MOHIGUL ISTAMKULOVA; KHUDOYOR KELDIYAROV; ASADULLO DAMINOV; NURALI MUKHAMADIEV; GAVHAR DUSHANOVA; DAVRON KHAYITOV; YUNUS RUZIEV; ISKANDAR RAYIMQULOV; ROKHILA JURAEVA; UMIDA NORBOYEVA (Society for Indonesian Biodiversity, 2025)
Abstract. Istamkulova M, Keldiyarov K, Daminov A, Mukhamadiev N, Dushanova G, Khayitov D, Ruziev Y, Rayimqulov I, Jurayeva R, Norboyeva U. 2025. Diversity and ecological determinants of essential oil composition of Achillea millefolium from various geobotanical areas of Samarkand, Uzbekistan. Biodiversitas 26: 3343-3355. Achillea millefolium is a well-known medicinal plant, widely distributed in Asia, Europe and North America. It is extensively used in traditional medicine and is valued for its broad spectrum of therapeutic properties. One of the key elements of its pharmacological value is its essential oil, which exhibits antimicrobial, antiparasitic, antioxidant, and other properties. This study explores the variation in the chemical composition of essential oils extracted from A. millefolium flowers collected in four distinct geobotanical areas of the Samarkand region, Uzbekistan: Amonkutan, Korabulok, Ilonsoy and Sazagan. Essential oils were obtained using the hydrodistillation method and their compositions were analyzed using gas chromatography-mass spectrometry. The results revealed significant qualitative and quantitative differences in essential oil compositions, primarily influenced by environmental factors. Essential oil variation reflects ecotypic local adaptation, highlighting its relevance for biodiversity and conservation efforts. These findings emphasize the influence of environmental factors such as altitude, precipitation, and soil pH on the chemotypic variability of A. millefolium. A total of 48 compounds were identified, with region-specific dominance: Ascaridole (20.43%) in Sazagan, Terpinolene (20.06%) in Amonkutan, m-Cymene (21.05%) in Korabulok, Camphor (2.86%) and 2-Carene (26.33%) in Ilonsoy. These constituents appear to play key roles in plant adaptation to local stress conditions. The identified relationships between environmental factors and the composition of plant essential oils enable the differentiation of chemotypes based on geographic characteristics and provide a basis for developing recommendations on optimal cultivation conditions, selective cultivation programs and standardization of raw materials for pharmacological applications.